Arresting bubble coarsening: A two-bubble experiment to investigate grain growth in the presence of surface elasticity. (9th January 2017) - Salonen, A.; Gay, C.; Maestro, A.; Drenckhan, W.; Rio, E.
Abstract: Many two-phase materials suffer from grain growth due to the energy cost which is associated with the interface that separates both phases. While our understanding of the driving forces and the dynamics of grain growth in different materials is well advanced by now, current research efforts address the question of how this process may be slowed down, or, ideally, arrested. We use a model system of two bubbles to explore how the presence of a finite surface elasticity may interfere with the coarsening process and the final grain size distribution. Combining experiments and modelling in the analysis of the evolution of two bubbles, we show that clear relationships can be predicted between the surface tension, the surface elasticity and the initial/final size ratio of the bubbles. We rationalise these relationships by the introduction of a modified Gibbs criterion . Besides their general interest, the present results have direct implications for our understanding of foam stability.